The cost incurred by victims of bullying from a societal perspective: estimates based on a German online survey of adolescents - Jantzer, Vanessa; Parzer, Peter; Resch, Franz; Kaess, Michael (European child & adolescent psychiatry, 2019)
Being a victim of bullying is linked to various social, emotional and behavioral problems potentially leading to a reduced quality of life. Furthermore, victims of bullying may cause extensive costs for society, for example by an above-average need for healthcare services. The present study was designed to quantify the costs and the loss of quality of life attributable to bullying by comparing victims with a control group of non-bullied students. A cross-sectional sample of 1293 adolescents (mean age 14.07, SD = 1.36) and their parents reported on bullying victimization, quality of life (adolescents’ self-report), and annual direct (medical and non-medical) as well as indirect costs (parents’ self-report) from a societal perspective (all expressed in €, year 2014 and 2015). For frequent (20.6% of our sample; costs: €8461.80 p.a.) but not occasional (13.3%; costs: €2850.06) bullying, victimization was associated with significantly higher costs compared to non-bullied adolescents (costs: €3138.00; annual difference between frequently bullied students and controls: €5323.01 p.a.; p = 0.008). Cost drivers included increased direct medical costs, but mostly indirect costs caused by productivity losses of the parents. Self-reported quality of life of frequent victims was considerably reduced (T = − 10.96; p < 0.001); also occasional bullying showed significantly reduced values in global quality of life (T = − 5.73; p < 0.001). The present findings demonstrate that frequent bullying is associated with substantial cost to society and reduced quality of life of victims. This observation underscores the need for effective school-based bullying prevention and suggests a high potential of effective programs to be cost effective as well.
First Online: 17 September 2018
Gesehen am 30.01.2020